Prevalence of Necrotizing Enterocolitis, Clinical Features and Management of Newborn at Vajira Hospital - Konjanat, Jitlada (Vajira Medical Journal : Journal of Urban Medicine, 2022)
Objective: The aim of this study was to evaluate the clinical features, affecting factors and treatment of necrotizing enterocolitis in newborn patients during 5 year period. Methods: A retrospective study of neonates with necrotizing enterocolitis treated at Vajira hospital between 1 January 2016-31 December 2020 were reviewed. Patients were analyzed for demographic data, clinical features, radiographic findings and the treatment. Results: A total 67 neonates were diagnosed NEC. Mean gestational age of the patients was 30.2±3.869 weeks. Mean birth weight of the patients was 1480.1±708.463 grams. Mean age at presentation was 9.2±5.23 days. The abnormal radiographic findings include intestinal dilatation was found in 63 cases (94%), pneumatosis intestinalis in 6 cases (8.9%), pneumoperitoneum can be seen in 3 patients (4.4%) with intestinal perforation. Forty-nine patients (73.2%) were classified in NEC stage I and the patients were managed with medical treatment. Eight patients (12%) were managed with surgical treatment and 3 cases were die. The mortality rate of the total 8 operated patients was 37.5% Conclusion: Necrotizing enterocolitis is a various clinical presentation includes nonspecific sign and symptoms, more specific symptom include abdominal distension, feeding intolerance and hematochezia. The umbilical catheterization and pneumatosis intestinalis from radiographic finding are the factors that has been associated the severity of necrotizing enterocolitis. Most patients can be managed with conservative treatment. Early recognition and aggressive treatment can decrease complications.